Pb(2+) tolerance by Frankia sp. strain EAN1pec involves surface-binding - Furnholm, Teal (Microbiology (Reading), 2017)
Several Frankia strains have been shown to be lead-resistant. The mechanism of lead resistance was investigated for Frankia sp. strain EAN1pec. Analysis of the cultures by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDAX) and Fourier transforming infrared spectroscopy (FTIR) demonstrated that Frankia sp. strain EAN1pec undergoes surface modifications and binds high quantities of Pb(+2). Both labelled and unlabelled shotgun proteomics approaches were used to determine changes in Frankia sp. strain EAN1pec protein expression in response to lead and zinc. Pb(2+) specifically induced changes in exopolysaccharides, the stringent response, and the phosphate (pho) regulon. Two metal transporters (a Cu(2+)-ATPase and cation diffusion facilitator), as well as several hypothetical transporters, were also upregulated and may be involved in metal export. The exported Pb(2+) may be precipitated at the cell surface by an upregulated polyphosphate kinase, undecaprenyl diphosphate synthase and inorganic diphosphatase. A variety of metal chaperones for ensuring correct cofactor placement were also upregulated with both Pb(+2) and Zn(+2) stress. Thus, this Pb(+2) resistance mechanism is similar to other characterized systems. The cumulative interplay of these many mechanisms may explain the extraordinary resilience of Frankia sp. strain EAN1pec to Pb(+2). A potential transcription factor (DUF156) binding site was identified in association with several proteins identified as upregulated with heavy metals. This site was also discovered, for the first time, in thousands of other organisms across two kingdoms.